Studies on Syngas Fermentation With Clostridium carboxidivorans in Stirred-Tank Reactors With Defined Gas Impurities - Rückel, Anton; Hannemann, Jens; Maierhofer, Carolin; Fuchs, Alexander; Weuster-Botz, Dirk (Frontiers in Microbiology, 2021)
Syngas fermentation processes with acetogenic bacteria like Clostridium carboxidivorans have been proven to be a promising approach for the conversion of CO-rich waste gases into short- and medium-chain alcohols. The challenge of synthesis gas impurities, on the other hand, has always been a major concern for establishing an industrial-scale process, since some of the trace components in waste gases, such as NH3, H2S, and NOx, can have inhibiting or even toxic effects on microbial growth and product formation. Thus, this study aims to identify the effects of the main trace impurities in syngas from gasification of biogenic residues by the supply of defined concentrations of trace impurities to the cultivation medium. Autotrophic gas fermentation studies were performed with C. carboxidivorans in batch-operated fully-controlled stirred-tank bioreactors with continuous gas supply (80% CO and 20% CO2). The syngas components NH3 and H2S had a positive effect on both growth and alcohol formation (ethanol, 1-butanol, and 1-hexanol). The maximum biomass concentration was increased by more than 50%, and the maximum ethanol concentration was more than doubled with 5.0 g L−1 NH4Cl or 1.0 g L−1 H2S provided by the addition of 2.2 g L−1 thioacetamide. The addition of the nitrogen oxide species nitrate and nitrite, on the other hand, reduced biomass growth as well as alcohol concentrations. Already, the supply of 0.1 g L−1 NaNO3 resulted in reduced growth and 25% reduction of the maximum ethanol concentration. The production of the longer chain alcohols 1-butanol and 1-hexanol was reduced as well. All NaNO2 concentrations tested showed a strong toxic effect on the metabolism of C. carboxidivorans, and neither CO consumption nor product formation was observed after addition. As a consequence, NOx components in syngas from the gasification of biogenic residues should be reduced by the gasification process and/or selectively removed from the syngas after gasification.